Sofosbuvir and ledipasvir for HIV/HCV co-infected patients. (23rd March 2016) - Rosenthal, Elana S.; Kottilil, Shyam; Polis, Michael A.
ABSTRACT: Introduction: Hepatitis C virus (HCV) is a chronic infection that disproportionately impacts people living with HIV. In the past, HCV therapy was less effective in individuals with HIV co-infection. However, the advent of direct-acting antivirals has revolutionized HCV treatment with high rates of success in patients both with and without HIV. Areas covered: In this paper, we review the evidence supporting the use of ledipasvir and sofosbuvir (LDV/SOF) for the treatment of HCV in patients with HIV co-infection. Articles searchable on MEDLINE/PubMed were reviewed to provide context for use of LDV/SOF in individuals with HCV and HIV co-infection. Expert opinion: This treatment is highly effective in achieving HCV cure or sustained virologic response, however further studies need to done to address efficacy of treatment in people with uncontrolled HIV, concerns regarding drug-interactions with antiretroviral therapy, and potential for shorter duration treatment.